Effects of Electrical Stimulation on Skeletal Muscle of Old Sedentary People. (6th April 2018) - Mosole, Simone; Zampieri, Sandra; Furlan, Sandra; Carraro, Ugo; Löefler, Stefan; Kern, Helmut; Volpe, Pompeo; Nori, Alessandra
Physical activity plays an important role in preventing muscle atrophy and chronic diseases in adults and in the elderly. Calcium (Ca 2+ ) cycling and activation of specific molecular pathways are essential in contraction-induced muscle adaptation. This study attains human muscle sections and total homogenates prepared from biopsies obtained before (control) and after 9 weeks of training by electrical stimulation (ES) on a group of volunteers. The aim of the study was to investigate about the molecular mechanisms that support functional muscle improvement by ES. Evidences of kinase/phosphatase pathways activation after ES were obtained. Moreover, expression of Sarcalumenin, Calsequestrin and sarco/endoplasmic reticulum Ca 2+ -ATPase (Serca) isoforms was regulated by training. In conclusion, this work shows that neuromuscular ES applied to vastus lateralis muscle of sedentary seniors combines fiber remodeling with activation of Ca 2+ -Calmodulin molecular pathways and modulation of key Ca 2+ -handling proteins.